(3CbQHGPjf GdbdGfSis - (3eMeO Hf HgQGe Hf eMeO GdbdGfSj GdSeQbfOj, HOQGdOjf , J (B590 (3g` s; (3HOQ GdOjf eMeO Hf HgQGe Hf eMeO GdbdGfSj GdSeQbfOj,J (B590 (3g` s ((3CfhQi s)
(3ChdgG (B:s
(3C(B/(3G HYO , abO OYGfi Edi LeY gPG GdeNJUQ Cfi QCjJ Ld GdbQHGPjfGJ eTMhfI ef fSN GdCOhfjI GdeQcHI s
(3BNQgG (B:s
(3ai efLGJg ef WHGFY GdMjhGf hNhGUgG (B: (3bO LQH gPG aUM hjbdd GdScQ LOkG s
(3GdfSNI HgG MhGTs
(3LeYI ef GdcJH JGdeTghQI GdeYJeOIs
(3YGdbGfhf hGdMGhi hGdcGed GdefUhQi hGdPNjQI hGdcaGjI haQOhS GdMceI hPcQ ajgG GdCTjGA GdYdejI NHQgG HGgJs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs